Persepsi Guru Pendidikan Jasmani SMP Negeri Se Purwakarta Terhadap Pembelajaran Jarak Jauh Pada Masa Pandemi - Revaldy Hidayat; Setio Nugroho; Rahmat Iqbal (Peneliti.net, 2021)
This study aims to find out what the perception of physical education teachers at State Junior High Schools in Purwakarta Regency towards distance learning during the covid 19 pandemic. This type of research is a descriptive study. Survey research method with data collection techniques using a questionnaire. The population in this study were PJOK teachers at SMPN 1, 2, 3, 4, 5 Purwakarta, totaling 13 teachers. Data analysis used descriptive analysis which was poured into percentage form. The results of this study indicate that the perception of physical education teachers at public junior high schools in Purwakarta district towards distance learning during the covid 19 pandemic is in the